PERANAN ORANG-TUA DALAM MENINGKATKAN KEPATUHAN SISWI MINUM TABLET ZAT BESI FOLAT DI KOTA-DEPOK - Apriningsih, Apriningsih; Madanijah, Siti; Dwiriani, Cesilia Meti; Kolopaking, Risatianti (GIZI INDONESIA, 2019)
One strategy to reduce anemia in adolescent girl age was through school-based iron folic-acid supplementation. Parents have the important role in improving the female students’ compliance. This study aim to identify parent’s knowledge, attitude and their role to improve female student’s compliance to consume iron folic-acid tablets, mechanism and supplementation period and female student’s compliance. Using a cross sectional design, 135 parents had  involved for 3 months from 9 high-schools in Depok area.The majority of respondents had less knowledge (54.1%) and never received socialization (61.5%). T-test and correlation test were applied. There were correlations between parent’s knowledge and attitude toward student’s compliance (p=0.00). The differences was found in female student’s compliance between parents who supervised when drinking at home with those who was not supervised (p = 0,000) and between parents who received socialization about anemia and those who never received (p = 0,000). The multivariate statistical results showed a fit regression equation about parents’ role in improving female student’s compliance to consume iron supplement (p value = 0.000). The regression model shows the greatest influence factor for female sudent’s compliance to consume iron folic-acid with supervision at home (ß=0.709, p=0.000), parent’s experience got socialization, tablet distribution mechanism and supplemantation schedule of giving iron folic acid (ß = 0.551, p=0.01, ß=0.435, p=0.01 and ß=0.429, p=0.00 respectively). It is suggested that school needs to involve parents in the program.